SnO2‐SiO2 1D Core‐Shell Nanowires Heterostructures for Selective Hydrogen Sensing. Issue 17 (3rd August 2021) - Raza, Muhammad Hamid; Kaur, Navpreet; Comini, Elisabetta; Pinna, Nicola
Abstract: SnO2 is one of the most employed n ‐type semiconducting metal oxide in chemo‐resistive gas‐sensing although it presents serious limitations due to a low selectivity. Herein, the authors introduce 1D SnO2 ‐SiO2 core‐shell nanowires (CSNWs). The amorphous SiO2 ‐shell layer with varying thicknesses (1.8–10.5 nm) is grown onto the SnO2 nanowires (NWs) by atomic layer deposition (ALD). SiO2 ‐coated SnO2 CSNWs show a dramatic improvement of the selectivity towards hydrogen. Moreover, the sensing‐response is strongly correlated to the thickness of the SiO2 ‐shell and the working temperature. The SnO2 ‐SiO2 CSNWs sensor with a 4.8‐nm SiO2 shell thickness exhibits the best selectivity and sensitivity, having ca. 7‐fold higher response toward hydrogen compared to bare‐SnO2 NWs. The selectivity and enhanced sensing‐response are related to the masking effect of the SiO2 shell and an increase in the width of the electron‐depletion‐layer due to a strong electronic coupling between the SnO2 core and SiO2 coating, respectively. Abstract : The gas‐sensing properties and the underlying transduction mechanism of well‐defined SnO2 ‐SiO2 core‐shell nanowires heterostructures with varying thickness of the amorphous SiO2 ‐shell layer (1.8–10.5 nm in thickness) are presented. The selectivity and response of SnO2 sensors are greatly enhanced by a conformal and homogeneous SiO2 coating of a calibrated thickness.